Navigating exercise attitudes and emotional positivity in adulthood during the COVID-19 pandemic: evidence from Shandong Province - Meng, Ran; Dong, Chen (Frontiers in Psychology, 2025)
IntroductionDuring the onset of the COVID-19 pandemic, understanding public attitudes and emotional responses towards physical exercise became crucial. This study aimed to explore the relationship between positive emotions and attitudes towards physical exercise among adults in Shandong Province, China, and to identify the influence of demographic factors such as gender, age, and education levels on these attitudes and emotions.MethodsA cross-sectional study was conducted among 404 adults in Shandong Province, China. Data were collected through surveys that assessed participants’ attitudes towards physical exercise and their emotional positivity. Quantitative analysis was performed to examine the correlations and differences based on demographic variables, including gender, age, and education levels.ResultsA robust positive correlation was found between positive emotions and attitudes towards physical exercise, with an emotional positivity ratio of 2.01±1.38% among respondents. Significant differences in attitudes and emotional positivity were observed based on demographic factors. Specifically, male participants had a higher mean score in behavioral intention and control compared to females. Older adults (>41 years) demonstrated more positive exercise attitudes, with a higher total score of 4.05 ± 0.54 compared to younger age groups. Additionally, respondents with a graduate degree and above reported the highest emotional positivity rate, outpacing those with lower educational levels.DiscussionThe findings indicate that demographic factors, including gender, age, and education levels, play a crucial role in shaping attitudes and emotional responses towards exercise, especially during a global health crisis. These insights highlight the importance of considering demographic differences when promoting physical exercise and designing public health interventions. Future research should further explore the underlying mechanisms and potential interventions to enhance positive attitudes and emotional responses towards physical exercise across diverse populations.